Ius Constituendum Criminal Asset Confiscation: Corrective Justice Orientation In Enforcement Of Corruption Criminal Acts - Asgar, Mochamad Ali (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Corruption in Indonesia, as an extraordinary crime that harms the state and society, requires a more effective legal approach through strengthening the ius constituendum related to asset forfeiture oriented towards corrective justice, while still paying attention to aspects of human rights and the principle of due process of law. This research aims to analyze the application of the ius constituendum concept of asset forfeiture oriented towards corrective justice in the enforcement of corruption crimes in Indonesia, as well as to identify challenges and opportunities for its implementation. This research uses normative legal research method with conceptual and statutory approaches, analyzes primary, secondary, and tertiary legal materials through literature study, and applies prescriptive and evaluative analysis techniques to examine the application of corrective justice-oriented asset forfeiture in the enforcement of corruption in Indonesia. The results show that the ius constituendum concept of corrective justice-oriented asset forfeiture can be applied in the enforcement of corruption crimes in Indonesia through several ways, such as simplifying the asset forfeiture process, expanding the authority of non-conviction-based asset forfeiture, implementing temporary asset forfeiture, and updating regulations. The implementation of this concept is faced with challenges such as regulatory limitations, evidentiary difficulties, and bureaucratic obstacles, but also opens up opportunities to increase the effectiveness of state asset recovery, adopt international best practices, and strengthen the legal framework. By addressing the challenges and capitalizing on the opportunities, Indonesia can build a fairer and more effective corruption eradication system.